Ferritic Stainless Steel Sheet
A ferritic stainless steel sheet with controlled crystal orientation and enhanced Al and Si content, along with Ni, addresses the challenge of maintaining magnetic properties and corrosion resistance, offering improved performance in both DC and AC magnetic fields.
Patent Information
- Application Number
- JP2021002032
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-01-08
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2041-01-08
AI Technical Summary
Ferritic stainless steel sheets face challenges in achieving sufficient magnetic properties, particularly in high-frequency ranges, while maintaining corrosion resistance due to low Al and Si content, which affect electrical resistivity and eddy current-induced iron loss.
A ferritic stainless steel composition with controlled crystal orientation and specific element additions, including Al and Si in excess of 0.50%, along with Ni, to enhance magnetic properties and corrosion resistance, combined with precise heat treatment and rolling processes to manage grain growth.
The solution provides a ferritic stainless steel sheet with excellent corrosion resistance and improved magnetic properties in both DC and AC magnetic fields, suitable for applications requiring strong magnetic characteristics.
Smart Images

Figure 0007621121000001 
Figure 0007621121000002 
Figure 0007621121000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a ferritic stainless steel sheet. [Background technology]
[0002] Ferritic stainless steel sheets are used in a wide range of fields, including home appliances, electronic devices, automobiles, etc. In particular, in fields where materials are exposed to high temperatures, such as heating equipment, kitchen equipment, and the automobile field, the stainless steels used are required to have oxidation resistance and corrosion resistance.
[0003] Additionally, magnetic properties are important for motor cases that house stepping motors, hysteresis motors, etc., motor components such as motor cores, sensors such as electronic throttle sensors and EPS sensors, injectors, relays, solenoid valves, and their cores, yokes, connectors, housings, etc. In particular, magnetic properties in an AC magnetic field are important for motor cases and motor components, as the positive and negative electrodes inside them frequently switch.
[0004] Specifically, the magnetic properties are determined from the values of saturation magnetic flux density (Bs), magnetic permeability (μ), residual magnetic flux density (Br), and coercive force (Hc). Saturation magnetic flux density Bs is an index showing the absolute value of the magnetic force of the material, and is the saturation magnetization that converges at a sufficiently large magnetic field H (A / m). The larger the saturation magnetic flux density Bs, the stronger the magnetic capacity to shield a strong magnetic field. Furthermore, magnetic permeability μ is an index of sensitivity to magnetic fields, and is calculated by the gradient (μ=B / H) of magnetization B (T) relative to the magnetic field H (A / m). The higher the magnetic permeability μ, the more sensitive the material is to magnetic fields and the easier it is to magnetize. Furthermore, residual magnetic flux density Br is the magnetic flux density remaining in the material when the magnetic field H is reduced to 0 from the state of saturation magnetic flux density Bs. Furthermore, coercive force Hc is the magnetic field value when the material is further demagnetized from this state and the magnetic flux density becomes 0. The smaller both the residual magnetic flux density Br and the coercive force Hc are, the easier it is to remove the magnetization.
[0005] In addition, when it comes to magnetic properties in an AC magnetic field, the maximum magnetic flux density (Bm) at each frequency and the iron loss (W) that affects this value are important. Increasing the content of Fe, Ni, and Co is effective in increasing the maximum magnetic flux density, and in stainless steel, the Fe content can be increased relatively by decreasing the Cr content. However, decreasing the Cr content decreases the corrosion resistance, which is the most important property of stainless steel. Moreover, the cause of increased iron loss is eddy currents induced within the magnetic material. Increasing electrical resistivity is an effective way to reduce losses due to eddy currents. For example, high Cr-containing ferritic stainless steels have a tendency to have higher magnetic flux density at high frequencies because their high Cr content increases electrical resistivity and reduces iron loss, but it is still difficult to prevent a decrease in magnetic flux density at frequencies above 1 kHz. Adding Al or Si is effective in further increasing electrical resistivity, but adding Al or Si to high Cr-containing ferritic stainless steels reduces toughness and workability.
[0006] Patent Document 1 describes a ferritic stainless steel sheet with excellent magnetic properties, which contains, by weight, C≦0.01%, Si: 0.1-0.6%, Mn: 0.1-1.0%, S≦0.004%, Cr: 5-13%, Ti: 0.05-0.5%, O≦0.004%, N≦0.015%, C+N≦0.015%, the balance being Fe and unavoidable impurities, the sum of the (111) plane intensities in the surface layer and center layer being 10 or less, and the maximum relative magnetic permeability ≧4000. Compared to copper, copper alloys, or ceramics, it has excellent impact resistance and magnetic properties, but the Al and Si contents are low, and sufficient magnetic flux density cannot be ensured in the high frequency range.
[0007] Patent Document 2 describes a ferritic stainless steel sheet having excellent magnetic properties, which is produced by hot rolling a slab containing, by weight, 0.015% or less C, 0.015% or less N, 1.5% or less Si, 1.0% or less Mn, 10-14% Cr, and 0.05-0.30% Ti into a hot-rolled sheet, cold rolling the hot-rolled sheet at a rolling reduction of 20-60%, and then annealing at 800-930° C. Compared with copper, copper alloys, or ceramics, this has excellent impact resistance and magnetic properties, but the Al and Si contents are low, and sufficient magnetic flux density cannot be ensured in the high frequency range.
[0008] Patent Document 3 discloses a highly corrosion-resistant magnetic stainless steel containing C: 0.015 wt% or less, Si: 0.30 wt% or less, Mn: 0.30 wt% or less, Cr: 10.0 to 20.0 wt%, Mo: 0.5 to 2.0 wt%, Ti: 0.05 to 0.30 wt%, Cu: 0.3 to 1.5 wt%, Al: 0.05 to 1.5 wt%, and the remainder essentially Fe, with corrosion resistance being ensured by the addition of Mo and Cu.
[0009] Patent Document 4 discloses a highly cold-forged magnetic stainless steel containing C: 0.02% or less, Si: 0.01 to 0.50%, Mn: 0.01 to 0.50%, Cr: 7.00 to 20.00%, Mo: 0.30 to 2.00%, Cu: 0.10 to 2.00%, Ti: 0.05 to 0.50%, Al: 0.05 to 3.00%, B: 0.0005 to 0.05%, N: 0.05% or less, with the balance being essentially Fe, and corrosion resistance is ensured by the combined addition of Ti, B, Mo, and Cu.
[0010] Patent Document 5 discloses a ferritic stainless steel sheet with excellent magnetic properties which contains, by mass%, C: 0.020% or less, Si: 1.00% or less, Mn: 1.00% or less, P: 0.035% or less, S: 0.0030% or less, Cr: 10.0 to 18.0%, N: 0.020% or less, Nb: 0.5% or less, Ti: 0.5% or less, Al: 0.10% or less, with the balance being Fe and impurities, and which has a texture on the sheet surface that satisfies the following (i) and (ii): (i) The angle between the normal direction of the steel sheet surface and the {110} plane orientation on the sheet surface is within 15°. The area ratio of grains with {110}±15° orientation is more than 3.0% and less than 30%. (ii) On the plate surface, the area ratio of the {110}±15° oriented grains is A, and the area ratio of the {111}±15° oriented grains is B. When the area ratio of the grain size is B, 0.10
[0011] Patent Document 6 discloses a ferritic stainless steel with excellent magnetic properties, characterized by containing, by mass%, C: 0.020% or less, Si: 1.00% or less, Mn: 1.00% or less, P: 0.035% or less, S: 0.0030% or less, Cr: 10.0 to 18.0%, N: 0.020% or less, Nb: 0.5% or less, Ti: 0.5% or less, Al: 0.10% or less, Sn: 0.001 to 0.5%, B: 0.005% or less, with the balance being Fe and impurities. [Prior art documents] [Patent documents]
[0012] [Patent Document 1] Patent No. 3629102 [Patent Document 2] Japanese Patent Application Publication No. 11-61255 [Patent Document 3] Japanese Unexamined Patent Publication No. 2-305944 [Patent Document 4] Japanese Patent Application Publication No. 4-318153 [Patent Document 5] JP 2020-63473 A [Patent Document 6] JP 2020-63472 A Summary of the Invention [Problem to be solved by the invention]
[0013] The ferritic stainless steel sheet described in Patent Document 5 ensures magnetic properties by controlling the crystal orientation, but since no Ni is added and the Al content is low, sufficient magnetic properties may not be ensured. The ferritic stainless steel sheet described in Patent Document 6 has improved magnetic properties by adding Sn, which is a grain boundary segregation element, to suppress grain boundary segregation of P, S, etc., but because no Ni is added and the Al content is low, there are cases in which sufficient magnetic flux density cannot be ensured, as with the ferritic stainless steel sheet described in Patent Document 5.
[0014] The present invention has been made in consideration of the above circumstances, and an object of the present invention is to provide a ferritic stainless steel sheet that has excellent corrosion resistance and is capable of exhibiting excellent magnetic properties in DC and AC magnetic fields. [Means for solving the problem]
[0015] In order to solve the above problems, the present invention has the following configuration. [1] In mass percent, C: 0.001 to 0.030%, Si: 0.01 to 3.00%, Mn: 0.01 to 2.00%, P: 0.030% or less, S: 0.0050% or less, Ni: 0.05-3.00%, Cr: 5.0-18.0%, Al: 0.054 ~5.000%, V: 0.001 to 1.000%, B: 0.0001 to 0.0100%, and N: Contains 0.001 to 0.030% Further, the alloy contains one or both of Ti: 0.01 to 0.30% and Nb: 0.001 to 0.60%, with the balance being Fe and impurities, and satisfies Si+Al≧0.50 or more; A ferritic stainless steel sheet characterized in that the texture on the sheet surface satisfies the following (a) to (c): (a) The area ratio of grains with {110}±15° orientation on the sheet surface, in which the angle between the normal direction to the steel sheet surface and the {110} plane orientation is within 15°, is more than 2.0% and less than 20.0%. (b) The area ratio of grains oriented in the {100}±15° direction, in which the angle between the normal direction to the steel sheet surface and the {100} plane orientation is within 15°, is more than 2.0% and less than 20.0%. (c) On the sheet surface, the area ratio of grains oriented at {110}±15° is defined as A, the area ratio of grains oriented at {100}±15° is defined as B, and the area ratio of grains oriented at {111}±15° on the sheet surface, where the angle difference between the normal direction to the steel sheet surface and the {111} plane orientation is within 15°, is defined as C / (A+B)≦15.0. [2] In addition, a part of Fe is replaced with, by mass%, Mo: 0.01 to 3.00%, Sn: 0.001 to 3.00%, Cu: 0.01-3.00%, W: 0.001 to 1.00%, Sb: 0.001 to 0.100%, Co: 0.001 to 0.500%, Ca: 0.0001 to 0.0050%, Mg: 0.0001 to 0.0050%, Zr: 0.0001 to 0.0300%, Ga: 0.0001 to 0.0100%, Ta: 0.001 to 0.050%, REM: 0.001 to 0.100% The ferritic stainless steel sheet according to [1], characterized in that it contains one or more of the following: Effect of the Invention
[0016] According to the present invention, it is possible to provide a ferritic stainless steel sheet which has excellent corrosion resistance and is capable of exhibiting excellent magnetic properties in a DC magnetic field and an AC magnetic field. Furthermore, the ferritic stainless steel sheet of the present invention can be suitably used for injector housings, injector parts, motor cases for accommodating stepping motors, hysteresis motors, etc., motor parts such as motor cores, sensors such as electronic throttle sensors and EPS sensors, injectors, relays, solenoid valves, as well as their cores, yokes, connectors, housings, etc. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] The present inventors have conducted extensive research with the aim of providing a ferritic stainless steel sheet that is excellent in corrosion resistance and capable of exhibiting excellent magnetic properties in a DC magnetic field and an AC magnetic field. As a result, they have made the following findings, which have led to the present invention.
[0018] First, it was found that in stainless steel with a relatively low Cr content of 5 to 18% (hereinafter also referred to as low Cr steel or low Cr steel), the corrosion resistance improves as the Al and Si contents increase. Thus, by adding a large amount of Al and Si, which also effectively act to improve electrical resistivity, to low Cr steel, which has excellent toughness and workability, it is possible to improve the electrical resistivity and corrosion resistance, which are issues with low Cr steel, while ensuring good toughness and workability. In other words, by adding a predetermined amount of Al and Si to low Cr steel, it is possible to provide a ferritic stainless steel that is superior in magnetic properties in an AC magnetic field and has good corrosion resistance compared to conventional steels. Specifically, the ferritic stainless steel sheet according to the present invention can be obtained by making Si+Al≧0.50.
[0019] It was also found that by adding Ni in addition to Al and Si, it is possible to simultaneously achieve improvements in corrosion resistance, toughness, and magnetic properties. It has been known for some time that Ni improves the above three properties, but we have found that the effect of adding Ni is particularly pronounced in the low Cr, high Al, and Si-containing ferritic stainless steel of the present invention, and that this effect is also very beneficial. With regard to corrosion resistance, this is thought to be because the effect of suppressing active dissolution by adding Ni is greater than that of high Cr steel, since the present invention is targeted at low Cr steel. In addition, Al and Si are elements that have the effect of reducing toughness and magnetic properties (saturation magnetic flux density), but Ni also has the effect of improving these toughness and magnetic properties. In other words, Ni is an important element that can improve both the toughness and magnetic properties of the ferritic stainless steel of the present invention.
[0020] Furthermore, they found that the magnetic properties of ferritic stainless steel can be improved by controlling the area ratios of {110}±15° oriented grains, {100}±15° oriented grains, and {111}±15° oriented grains within specified ranges in the texture on the sheet surface.
[0021] A specific method for controlling the texture is as follows: first, the annealing temperature during hot-rolled sheet annealing is set to 950°C or higher to coarsen the grain size and increase the area ratio of grains with {100} plane orientation. Next, the steel after hot-rolled sheet annealing is cold-rolled with a rolling reduction of 60% or more to accumulate a large amount of strain in the coarsened grains. This can promote recrystallization of grains with {110} plane orientation during cold-rolled sheet annealing. In other words, by appropriately controlling the conditions for hot-rolled sheet annealing to increase the ratio of grains with {100}±15° orientation, and then cold-rolling with a rolling reduction of 60% or more, sufficient recrystallized grains with {110}±15° plane orientation, which are effective for magnetic properties, can be generated during cold-rolled annealing. In addition, by setting the soaking temperature at 950°C or less during cold-rolled sheet annealing, it is possible to suppress the growth of crystal grains having {111} plane orientation, which has the effect of reducing magnetic properties and toughness. Furthermore, by setting the soaking temperature at 950°C or less during cold-rolled sheet annealing, it is possible to promote fine precipitation of precipitates such as FeTiP. These fine precipitates such as FeTiP have the effect of suppressing the growth of crystal grains having {111} plane orientation during magnetic annealing. However, if the soaking temperature is high, the precipitates such as FeTiP become coarse, and the effect of suppressing the growth of crystal grains having {111} plane orientation during magnetic annealing cannot be enjoyed. In other words, by appropriately controlling the soaking temperature at 950°C or less during cold-rolled sheet annealing, it is possible to promote the growth of crystal grains having {100} plane or {110} plane orientation, and to suppress the growth of crystal grains having {111} plane orientation during magnetic annealing, and as a result, it is possible to provide a ferritic stainless steel with excellent magnetic properties. The present inventors have found that the texture required for realizing such properties after magnetic annealing is a texture having the above-mentioned plane orientation ratio.
[0022] Regarding the contribution of Al and Si to corrosion resistance, Al is believed to dissolve as ions inside the early pit and then adsorb to the surface, thereby inhibiting pit growth and promoting repassivation. In addition, Si is believed to form an oxide inside the pit, inhibiting pit growth and promoting repassivation. However, while neither Al nor Si is effective enough in reducing the amount of active dissolution itself, it was found that adding Ni in combination with Al and Si can ensure the amount of active dissolution inhibition.
[0023] Furthermore, it is generally known that Fe-based oxides with low corrosion resistance are formed on the surface during oxidation by magnetic annealing, but it was found that when the ferritic stainless steel sheet of the present invention is subjected to magnetic annealing, the high Al and Si contents make it difficult for Fe-based oxides to form on the surface. In other words, in the present invention, Al and Si can also contribute to ensuring corrosion resistance after magnetic annealing.
[0024] Hereinafter, a ferritic stainless steel sheet according to one embodiment of the present invention will be described. The ferritic stainless steel sheet according to the present embodiment contains, by mass%, C: 0.001-0.030%, Si: 0.01-3.00%, Mn: 0.01-2.00%, P: 0.030% or less, S: 0.0050% or less, Ni: 0.05-3.00%, Cr: 5.0-18.0%, Al: 0.001-5.000%, V: 0.001-1.000%, B: 0.0001-0.0100%, N: 0.001-0.030%, and further contains one or two of Ti: 0.01-0.30% and Nb: 0.001-0.60%, with the balance being Fe and impurities, satisfies Si+Al≧0.50 or more, and the texture on the sheet surface satisfies the following (a) to (c). (a) The area ratio of grains with {110}±15° orientation on the sheet surface, in which the angle difference between the normal direction to the steel sheet surface and the {110} plane orientation is within 15°, is more than 2.0% and less than 20%. (b) The area ratio of grains with {100}±15° orientation on the sheet surface, in which the angle difference between the normal direction to the steel sheet surface and the {100} plane orientation is within 15°, is more than 2.0% and less than 20%. (c) When the area ratio of grains oriented at {110}±15° on the sheet surface is A, the area ratio of grains oriented at {100}±15° is B, and the area ratio of grains oriented at {111}±15° on the sheet surface, where the angle difference between the normal direction to the steel sheet surface and the {111} plane orientation is within 15°, C / (A+B)≦15.0. The chemical composition of the ferritic stainless steel sheet of this embodiment will be described below. Note that the "%" for the content of each element means mass %.
[0025] C: 0.001 to 0.030% C reduces magnetic properties, intergranular corrosion resistance, and workability, so its content must be kept low. Therefore, the C content is set to 0.030% or less. However, excessively lowering the C content increases refining costs, so the C content is set to 0.001% or more. The preferred lower limit of the C content is 0.002% or more, the more preferred upper limit is 0.003% or more, and the even more preferred upper limit is 0.004% or more. The preferred upper limit of the C content is 0.015% or less, and the more preferred upper limit is 0.010% or less.
[0026] Silicon: 0.01 to 3.00% Silicon dramatically improves magnetic properties, electrical resistivity, oxidation resistance at low and medium temperatures (500 to 700°C) and oxidation resistance at high temperatures (700°C or higher). It is also a very useful element that not only suppresses corrosion by concentrating on the surface, but also reduces the corrosion rate of the base material. Therefore, the content of silicon is set to 0.01% or more. However, since excessive silicon content reduces toughness, workability, and weld penetration, the content of silicon is set to 3.00% or less. The lower limit of the silicon content is preferably 0.05% or more, more preferably 0.10% or more, and even more preferably 0.4% or more. The upper limit of the silicon content is preferably 2.00% or less, more preferably 1.50% or less, and even more preferably 1.20% or less.
[0027] Mn: 0.01 to 2.00% Mn is useful as a deoxidizing element, but excessive Mn content deteriorates corrosion resistance. Therefore, the Mn content is set to 0.01 to 2.00%. The lower limit of the Mn content is preferably 0.05% or more, and more preferably 0.10% or more. The upper limit of the Mn content is preferably 1.00% or less, and more preferably 0.50% or less.
[0028] P:0.030% or less Since P is an element that deteriorates magnetic properties, workability, and weldability, the lower the content, the better. Therefore, the P content is set to 0.030% or less. The preferred range of the P content is 0.025% or less. However, an excessively low P content increases refining costs, so the P content may be set to 0.001% or more.
[0029] S: 0.0050% or less Since S deteriorates corrosion resistance, the lower the content, the better. Therefore, the S content is set to 0.0050% or less. The preferred range of the S content is 0.0030% or less. However, since an excessively low S content increases refining costs, the S content may be set to 0.0001% or more.
[0030] Ni: 0.05 to 3.00% Ni is an important element in this embodiment, and in order to improve the magnetic properties, corrosion resistance, and toughness in a DC magnetic field, it is necessary to include 0.05% or more. However, since a large amount of Ni content leads to an increase in alloy cost, the Ni content is set to 3.00% or less. The preferred lower limit of the Ni content is 0.06% or more, more preferably 0.10% or more, even more preferably 0.13% or more, and even more preferably 0.15% or more. The preferred upper limit of the Ni content is 2.50% or less, more preferably 2.00% or less, and even more preferably 1.50% or less.
[0031] Cr: 5.0~18.0% Cr content must be 5.0% or more to ensure oxidation resistance and corrosion resistance in salt damage environments. As the Cr content increases, oxidation resistance and corrosion resistance improve and electrical resistivity also increases, but the Cr content decreases the weld penetration, thermal conductivity, workability, toughness, and manufacturability, so the Cr content is set to 18.0% or less. The Cr content is preferably in the range of 7.5 to 15.0%, more preferably 9.0 to 13.0%.
[0032] Al: 0.001 to 5.000% Al is an important element in this embodiment. Al dramatically improves oxidation resistance, especially at high temperatures (700°C or higher). In addition, it is a very beneficial element that not only suppresses corrosion by concentrating on the steel surface, but also reduces the corrosion rate of the base material. Al also has the effect of increasing electrical resistivity and improving magnetic properties in an AC magnetic field. This effect is particularly noticeable in stainless steels with a low Cr content. Therefore, the Al content is set to 0.001% or more. However, since excessive Al content causes a decrease in the toughness and elongation of the material, and reduces the toughness and workability, the Al content is set to 5.000% or less. The preferred range of the Al content is 0.010 to 3.000%, and the more preferred range is 0.030 to 2.000%.
[0033] V: 0.001 to 1.000% V must be present in an amount of 0.001% or more to improve corrosion resistance. However, a large amount of V increases the alloy cost, so the V content is set to 1.000% or less. The V content is preferably in the range of 0.005 to 0.800%, and more preferably in the range of 0.010 to 0.500%.
[0034] B: 0.0001 to 0.0100% B is an element useful for improving secondary workability, and must be contained in an amount of 0.0100% or less. The lower limit of the B content is set to 0.0001% or more, at which a stable effect can be obtained. The B content is preferably in the range of 0.0005 to 0.0050%, and more preferably in the range of 0.0010 to 0.0030%.
[0035] N: 0.001 to 0.030% N is a useful element for pitting corrosion resistance, but it reduces magnetic properties, intergranular corrosion resistance, and workability. Therefore, it is necessary to keep the N content low. Therefore, the N content is set to 0.030% or less. However, an excessively low N content increases refining costs, so the N content is set to 0.001% or more. The preferred range of the N content is 0.002 to 0.020%.
[0036] One or both of Ti: 0.01-0.30% and Nb: 0.001-0.60% In order to prevent sensitization of stainless steel, Ti and Nb must be contained in an amount of 0.01% or more for Ti and 0.001% or more for Nb. However, a large content leads to an increase in alloy cost, a decrease in toughness, a decrease in corrosion resistance due to an increase in inclusions in the steel, and a decrease in manufacturability, so the Ti content is 0.30% or less and the Nb content is 0.60% or less. The Ti content is preferably in the range of 0.03 to 0.25%, more preferably in the range of 0.04 to 0.20%. The Nb content is preferably in the range of 0.03 to 0.55%, more preferably in the range of 0.04 to 0.50%. It is sufficient that either Ti or Nb is contained, and both Ti and Nb may be contained.
[0037] Regarding Al and Si, by satisfying the condition Si+Al≧0.50 (Al and Si are the mass % of each element in the ferritic stainless steel), excellent magnetic properties in an AC magnetic field and improved corrosion resistance can be achieved. The total content of Si and Al (Si+Al) is preferably 0.60 or more, and more preferably 0.70 or more.
[0038] The above is the basic chemical composition of the ferritic stainless steel sheet of this embodiment. In other words, other than the above elements, the composition is made up of Fe and impurities. However, in this embodiment, the following elements may be further contained as necessary.
[0039] Mo, Sn, Cu, W, Sb, Co, Ca, Mg, Zr, Ga, Ta, and REM may be contained alone or in combination depending on the purpose. The lower limit of these elements is 0% or more, and preferably more than 0%.
[0040] Mo: 0.01 to 3.00% Mo can be contained in an amount of 0.01% or more to improve corrosion resistance. However, excessive content of Mo deteriorates workability and is expensive, leading to increased costs. Therefore, the Mo content is set to 3.00% or less. The Mo content is preferably in the range of 0.05 to 2.00%, and more preferably in the range of 0.05 to 1.00%.
[0041] Sn: 0.001 to 3.00% Sn can be contained in an amount of 0.001% or more in order to improve corrosion resistance. However, excessive content leads to increased costs. Therefore, the Sn content is set to 3.00% or less. The preferred range of Sn content is 0.005 to 1.00%, and more preferably 0.010 to 1.00%.
[0042] Cu: 0.01-3.00% Cu can be contained in an amount of 0.01% or more to improve corrosion resistance. However, excessive content leads to increased costs. Therefore, the Cu content is set to 3.00% or less. The preferred range of Cu content is 0.02 to 1.00%, and the more preferred range is 0.05 to 0.09%.
[0043] W: 0.001 to 1.00% W can be contained in an amount of 1.00% or less in order to improve corrosion resistance. In order to obtain a stable effect, the W content is set to 0.001% or more. The preferred range of the W content is 0.005 to 0.80%.
[0044] Sb: 0.001 to 0.100% Sb can be contained in an amount of 0.100% or less in order to improve general corrosion resistance. In order to obtain a stable effect, the Sb content is set to 0.001% or more. The preferred range of the Sb content is 0.010 to 0.080%.
[0045] Co: 0.001 to 0.500% Co can be contained at 0.500% or less in order to improve secondary workability and toughness. In order to obtain a stable effect, the Co content is set to 0.001% or more. The preferred range of the Co content is 0.010 to 0.300%.
[0046] Ca: 0.0001 to 0.0050% Ca is contained for desulfurization, but if contained in excess, water-soluble inclusions CaS are generated, which reduces corrosion resistance. Therefore, Ca can be contained in the range of 0.0001 to 0.0050%. The preferred range of Ca content is 0.0005 to 0.0030%.
[0047] Mg: 0.0001 to 0.0050% Mg is useful for refining the structure and improving workability and toughness. Therefore, Mg can be contained in the range of 0.0050% or less. To obtain a stable effect, the Mg content is set to 0.0001% or more. The preferable range of the Mg content is 0.0005 to 0.0030%.
[0048] Zr: 0.0001 to 0.0300% Zr can be contained in an amount of 0.0300% or less in order to improve corrosion resistance. In order to obtain a stable effect, the Zr content is set to 0.0001% or more. The preferred range of the Zr content is 0.0010 to 0.0100%.
[0049] Ga: 0.0001 to 0.0100% Ga can be contained in an amount of 0.0100% or less in order to improve corrosion resistance and hydrogen embrittlement resistance. In order to obtain a stable effect, the Ga content is set to 0.0001% or more. The Ga content is preferably in the range of 0.0005 to 0.0050%.
[0050] Ta: 0.001 to 0.050% Ta can be contained in an amount of 0.050% or less in order to improve corrosion resistance. In order to obtain a stable effect, the Ta content is set to 0.001% or more. The preferred range of the Ta content is 0.005 to 0.030%.
[0051] REM: 0.001 to 0.100% REM has a deoxidizing effect and is therefore a useful element in refining, so it may be contained in an amount of 0.100% or less. In order to obtain a stable effect, the REM content is set to 0.001% or more. The preferred range of REM content is 0.003 to 0.050%. Here, REM (rare earth elements) is a general term for two elements, scandium (Sc) and yttrium (Y), and 15 elements (lanthanoids) from lanthanum (La) to lutetium (Lu), as generally defined. REM refers to one or more elements selected from these rare earth elements, and the REM content is the total amount of rare earth elements.
[0052] The ferritic stainless steel sheet of this embodiment is composed of Fe and impurities (including unavoidable impurities) other than the elements described above. The term "impurities" refers to those that are mixed in from raw materials such as ores, scraps, or the manufacturing environment when industrially manufacturing steel, and are acceptable within a range that does not adversely affect the steel sheet of the present invention. In addition to the elements described above, other elements may be contained within a range that does not impair the effects of the present invention. In this embodiment, for example, Bi, Pb, Se, H, etc. may be contained, but in that case, it is preferable to reduce them as much as possible. On the other hand, the content ratios of these elements are controlled to the extent that the problem of the present invention is solved, and Bi may be contained in an amount of 0.01% or less, Pb in an amount of 0.01% or less, Se in an amount of 0.01% or less, and H in an amount of 0.01% or less, as necessary.
[0053] Next, the texture of the ferritic stainless steel sheet of this embodiment will be described. The ferritic stainless steel sheet of this embodiment has a texture on the sheet surface that satisfies the following (a) to (c).
[0054] (a) The area ratio of grains with {110}±15° orientation on the sheet surface, in which the angle between the normal direction to the steel sheet surface and the {110} plane orientation is within 15°, is more than 2.0% and less than 20.0%. (b) The area ratio of grains oriented in the {100}±15° direction, in which the angle between the normal direction to the steel sheet surface and the {100} plane orientation is within 15°, is more than 2.0% and less than 20.0%. (c) On the plate surface, if the area ratio of grains oriented at {110}±15° is A, the area ratio of grains oriented at {100}±15° is B, and the area ratio of grains oriented at {111}±15° is C, then C / (A+B)≦15.0.
[0055] The {110} orientation is called the Goss orientation, and has good magnetic properties because the rolling direction coincides with the easy axis of magnetization of iron. In this embodiment, it has been found that it is effective to control the area ratio of {110}±15° orientation grains on the sheet surface. By including the area ratio of {110}±15° orientation grains in the range of more than 2.0% and less than 20.0%, it can contribute to the improvement of magnetic properties, especially magnetic properties in a direct current magnetic field. From the viewpoint of magnetic properties, the area ratio of {110}±15° orientation grains is preferably 5.0% or more, more preferably 7.0% or more. Note that the larger the area ratio of {110}±15° orientation grains, the better, but if it is excessively large, it becomes necessary to set the heat treatment temperature of the hot-rolled sheet to 1100°C or more as described below, and the descalability of the hot-rolled annealed sheet will be significantly deteriorated. Therefore, the area ratio of {110}±15° orientation grains is 20.0% or less, preferably 18.0% or more.
[0056] In addition, it has been found that, as with the {110}±15° orientation grains, it is effective to ensure a certain or higher area ratio from the viewpoint of magnetic properties in a DC magnetic field. The area ratio of the {100}±15° orientation grains is in the range of more than 2.0% and less than 20.0%, which can contribute to the improvement of magnetic properties in a DC magnetic field. From the viewpoint of magnetic properties, the area ratio of the {100}±15° orientation grains is preferably 5.0% or more, more preferably 7.0% or more. The larger the area ratio of the {100}±15° orientation grains, the better, but if it is excessively large, it becomes necessary to set the heat treatment temperature of the hot-rolled sheet to 1100°C or more as described below, and the descalability of the hot-rolled annealed sheet will be significantly deteriorated. Therefore, the area ratio of the {100}±15° orientation grains is 20.0% or less, preferably 18.0% or more.
[0057] In addition, when the area ratio of {110}±15° oriented grains on the sheet surface is A (%), the area ratio of {100}±15° oriented grains is B (%), and the area ratio of {111}±15° oriented grains on the sheet surface, where the angle difference between the normal direction to the steel sheet surface and the {111} plane orientation is within 15°, is C (%), from the viewpoint of magnetic properties in a DC magnetic field, it is effective to make C / (A+B)≦15.0.
[0058] The {111}±15° orientation grains are the main orientation of the recrystallized texture, and reducing the ratio of their area fraction C is effective in improving the magnetic properties. In other words, by reducing the ratio C / (A+B) of the sum (A+B) of the area fractions of the {110}±15° orientation grains and the {111}±15° orientation grains, which are effective in improving the magnetic properties, it is possible to improve the magnetic properties, particularly the magnetic properties in a DC magnetic field. Therefore, C / (A+B) should be 15.0 or less, and preferably 10.0.
[0059] Although there are no particular limitations on the area ratio C of the {111}±15° oriented grains, an excessively large ratio is likely to deteriorate the magnetic properties, and therefore it is preferable to set the ratio at 70% or less.
[0060] In this embodiment, the "plate surface" refers to the region from the surface of the steel plate to t / 8 of the thickness of the steel plate, where t is the thickness of the steel plate, and also refers to the region from the surface of the steel plate to a thickness of t / 8 in the surface direction on both sides of the steel plate.
[0061] The texture and its area fraction can be analyzed using electron backscatter diffraction (EBSD). The crystal orientation population that contributes to the magnetic properties can be quantified by displaying a crystal orientation map that divides the grains into three regions at the center of the sheet thickness: {100}±15° oriented grains, {110}±15° oriented grains, and {111}±15° oriented grains. For example, EBSD measurements are performed at a magnification of 100x on a plane parallel to the steel sheet surface in a measurement area of 800 μm in the sheet width direction and 2000 μm in the rolling direction, and a crystal orientation map of crystal grains whose angular difference between the normal direction of the plane parallel to the steel sheet surface and each of the {100} plane orientations, {110} plane orientations, and {111} plane orientations is within 15° (i.e., {100}±15° orientation grains, {110}±15° orientation grains, {111}±15° orientation grains±15° orientation grains) can be displayed, along with the area fraction of each.
[0062] The thickness of the ferritic stainless steel sheet according to this embodiment is not particularly limited, but may be 0.1 to 5.0 mm. By making the thickness of the ferritic stainless steel sheet 0.1 mm or more, it can be applied to various applications such as structural materials. The thickness of the ferritic stainless steel sheet is preferably 0.4 mm or more. Furthermore, by making the thickness 5.0 mm or less, it is possible to create a structure necessary for improving magnetic properties. The thickness of the ferritic stainless steel sheet is preferably 4.0 mm or less.
[0063] Next, a method for producing the ferritic stainless steel sheet according to this embodiment will be described.
[0064] The manufacturing method for the ferritic stainless steel sheet of this embodiment comprises the steps of steelmaking-hot rolling-annealing the hot-rolled sheet and pickling-cold rolling-annealing the cold-rolled sheet. The manufacturing conditions for each step may be appropriately determined as long as they do not impair the effects of the present invention. However, from the viewpoint of controlling the crystal plane orientation, it is necessary to appropriately control the conditions for the hot-rolled sheet annealing, the cold rolling reduction, and the cold-rolled sheet annealing. Each step and the conditions of the production method will be described in detail below.
[0065] In steelmaking, a suitable method is to melt steel containing the above-mentioned essential components and components added as required in a converter, followed by secondary refining. The melted steel is cast (continuous casting) into slabs. The slabs are heated to a specified temperature and hot-rolled to a specified plate thickness by continuous rolling. Considering the crystal orientation of the final product, the slab heating temperature is preferably 1190°C or higher and 1300°C or lower, and the slab thickness is preferably 3.0 mm or higher and 300.0 mm or lower.
[0066] The annealing process after hot rolling (hot-rolled sheet annealing process) is an important process for optimizing the crystal orientation and obtaining a structure with excellent magnetic properties. Specifically, the soaking temperature in the hot-rolled sheet annealing is 950°C to 1100°C. If the soaking temperature in the hot-rolled sheet annealing is less than 950°C, the growth of {100}±15° orientation grains, in which the angle difference between the normal direction of the steel sheet surface and the {100} plane orientation on the sheet surface is within 15°, becomes insufficient, so the soaking temperature is 950°C or more. In addition, if the soaking temperature in the hot-rolled sheet annealing is 1100°C or more, there is a risk of causing a decrease in toughness due to coarsening of crystal grains and a deterioration in descaling ability due to thickening of oxide scale, so the soaking temperature is 1100°C or less. Preferably, the soaking temperature in the hot-rolled sheet annealing is 980°C to 1080°C. The soaking time (holding time) in the hot-rolled sheet annealing is not particularly limited, but is preferably 10 seconds to 120 seconds from the viewpoint of completing recrystallization.
[0067] After the hot-rolled sheet annealing, pickling and cold rolling are carried out in this order. The reduction in the cold rolling is 60% or more. If the reduction is less than 60%, recrystallization may be insufficient during the subsequent cold-rolled sheet annealing. In particular, the reduction is 60% or more, preferably 65% or more, because there is a risk of insufficient recrystallization of {110}±15° orientation grains, in which the angle difference between the normal direction of the steel sheet surface and the {110} plane orientation is within 15° on the sheet surface. On the other hand, if the reduction is too high, productivity may deteriorate, so the reduction is preferably 95% or less.
[0068] The cold rolling after pickling may be performed using either a normal Sendzimir mill or a tandem mill, but Sendzimir mill rolling is preferable to suppress recrystallization of {111}±15° oriented grains, in which the angle difference between the normal direction of the steel sheet surface and the {111} plane orientation on the sheet surface is within 15°, during the subsequent cold-rolled sheet annealing process. In cold rolling, the roll roughness, roll diameter, rolling oil, number of rolling passes, rolling speed, rolling temperature, etc. may be appropriately selected within normal ranges. Intermediate annealing may be performed during cold rolling.
[0069] In the final annealing after cold rolling (cold-rolled sheet annealing), it is effective to set the soaking temperature to 950°C or less from the viewpoint of suppressing the growth of crystal grains having the above-mentioned {111} plane orientation. Furthermore, by setting the soaking temperature during cold-rolled sheet annealing to 950°C or less, fine precipitation of precipitates such as FeTiP can be promoted. Since these fine precipitates such as FeTiP have the effect of suppressing the growth of crystal grains having the {111} plane orientation during magnetic annealing, it is desirable to finely precipitate them during cold-rolled sheet annealing. That is, the soaking temperature of cold-rolled sheet annealing is important from the viewpoint of suppressing the growth of crystal grains having the {111} plane orientation and promoting fine precipitation of precipitates such as FeTiP. In particular, the soaking temperature needs to be 850°C to 950°C. If the soaking temperature of cold-rolled sheet annealing is less than 850°C, recrystallization may be insufficient, so the soaking temperature is 850°C or more. Furthermore, if the soaking temperature for annealing the cold-rolled sheet exceeds 950° C., the growth of the crystal grains having the {111} plane orientation may be insufficiently suppressed, so the soaking temperature is set to 950° C. or less. The soaking temperature for annealing the cold-rolled sheet is preferably 880° C. to 920° C. The soaking time (holding time) for annealing the cold-rolled sheet is not particularly limited, but is preferably 10 seconds to 120 seconds from the viewpoint of promoting recrystallization.
[0070] The intermediate annealing performed during cold rolling and the final annealing after cold rolling may be batch annealing or continuous annealing. The atmosphere of each annealing may be bright annealing in a non-oxidizing atmosphere such as hydrogen gas or nitrogen gas, if necessary, or annealing in air. After the final annealing, salt treatment, pickling, electrolytic pickling, etc. may be performed.
[0071] The ferritic stainless steel sheet according to this embodiment can be manufactured by the manufacturing method described above, but other processes may also be carried out as appropriate within the scope of the present invention without impairing the effects of the present invention. For example, after final annealing, a tension leveler process for shape correction may be carried out, or the sheet may be passed through.
[0072] The ferritic stainless steel sheet according to this embodiment can be suitably used in applications where magnetic properties are particularly required. In such cases, it is possible to produce products with excellent magnetic properties by subjecting the product to magnetic annealing after processing into parts. The conditions for magnetic annealing may be appropriately determined depending on the product and application, but for example, 1×10 -2 ~9×10 -2 It is preferable to carry out the magnetic annealing in a vacuum of 1 Pa at a heating rate of 1 to 100°C / min, a soaking temperature of 800 to 1000°C, and a soaking time of 1 to 10 hours, more preferably 1 to 3 hours. After such magnetic annealing, cooling with Ar gas or the like may be carried out, or air cooling or furnace cooling may be carried out. By carrying out such magnetic annealing, the removal of processing strain and the coarsening of crystal grains occur, improving the magnetic properties and improving the magnetic flux density. As a result, the magnetic properties in a DC magnetic field and an AC magnetic field can be improved.
[0073] The ferritic stainless steel sheet according to the present embodiment and a suitable method for producing the same have been described above, and the ferritic stainless steel sheet according to the present embodiment can provide a ferritic stainless steel sheet that is excellent in corrosion resistance and capable of exhibiting excellent magnetic properties in DC and AC magnetic fields. Furthermore, by subjecting the ferritic stainless steel sheet to an optimal magnetic annealing process, a ferritic stainless steel sheet that is excellent in corrosion resistance and magnetic properties in DC and AC magnetic fields and is suitable for applications requiring magnetic properties can be provided. EXAMPLES
[0074] The present invention will be described in more detail below based on examples, but the present invention is not limited to the conditions used in the following examples. Note that the underlines in the tables indicate items outside the scope of the present invention.
[0075] Steels having the compositions shown in Tables 1A and 1B were melted and hot-rolled into slabs with a thickness of 200 mm until the plate thickness reached 3 mm. The slab heating temperature was in the range of 1190 to 1300°C. In the tables, "-" indicates that no additive was intentionally added. Next, the hot-rolled steel sheet was subjected to a heat treatment (hot-rolled sheet annealing) for 60 seconds at the temperature shown in Tables 2A and 2B, and further to shot blasting and pickling. Then, cold rolling was performed using a Sendzimir mill at the rolling reduction shown in Tables 2A and 2B to obtain the sheet thickness shown in Tables 2A and 2B. Next, heat treatment (cold-rolled sheet annealing) was performed for 60 seconds at the temperature shown in Tables 2A and 2B, and then salt treatment and pickling were performed. Pickling was performed by electrolytic pickling in a solution with a nitric acid concentration of 150 g / L. In this manner, a ferritic stainless steel sheet was produced.
[0076] A test piece with a width of 75 mm and a length of 150 mm was cut from the center of the width direction of the prepared steel plate to prepare a test piece for the JASO-CCT test. The JASO-CCT test was performed for 12 cycles in accordance with JASO M 610-92. As the judgment criteria for the JASO-CCT test, the rating number was judged according to the method in accordance with JIS G 0595:2004, and "3" was set as the boundary value. Steel types with rating numbers of 4 to 9 were judged to have excellent corrosion resistance, and are indicated by the symbol "○" in Tables 2A and 2B. On the other hand, steel types with rating numbers of 0 to 3 were judged to have poor corrosion resistance, and are indicated by the symbol "×" in Tables 2A and 2B.
[0077] In addition, the crystal orientation of the steel was analyzed near the center of the width direction of the prepared steel sheets using electron backscatter diffraction (EBSD). The crystal orientation group that contributes to the magnetic properties was quantified by displaying a crystal orientation map that was divided into three regions at the center of the sheet thickness: {100}±15° oriented grains, {110}±15° oriented grains, and {111}±15° oriented grains. That is, EBSD measurements were performed at a magnification of 100x on a plane parallel to the steel sheet surface, over a measurement area of 800 μm in the sheet width direction and 2000 μm in the rolling direction, and a crystal orientation map of crystal grains whose angular difference between the normal direction of the plane parallel to the steel sheet surface and the {100} plane orientation, {110} plane orientation, and {111} plane orientation was within 15° (i.e., {100}±15° orientation grains, {110}±15° orientation grains, and {111}±15° orientation grains) was displayed and their area fractions were measured.
[0078] Furthermore, the following tests were carried out to evaluate the magnetic properties. First, 1.3 x 10 -2 The temperature was increased at a rate of 1 to 100° C. / min in a vacuum of 100 Pa, and magnetic annealing was performed for 2 hours at a magnetic annealing temperature of 950° C., and then air-cooled.
[0079] A ring sample with an outer diameter of 45 mm, an inner diameter of 33 mm, and a height of 0.8 mm was cut out by electrical discharge machining from near the center of the width direction of the steel sheet after magnetic annealing. This ring sample was covered with Kapton film, and 100 turns of secondary winding were wound around it, then it was stored in an acrylic case, and 200 turns of primary winding were wound around it to obtain a ring-shaped test sample for DC and AC magnetic measurements. DC magnetic measurements and AC magnetic measurements were performed using this ring-shaped test sample with a magnetic measuring device (Iwatsu Measurement Co., Ltd. BH Analyzer SY-8258).
[0080] As the DC magnetic measurement conditions, the initial magnetization curve up to 4 kA / m was measured, and the relative permeability was calculated using the following formula (1). The maximum value of the maximum relative permeability μ m asked for.
[0081] μ m = B / μ0H (1) (B: magnetic flux density, μ0: magnetic permeability of vacuum (4π×10 -7 H / m), H: magnetic field strength
[0082] Maximum relative permeability μ m If the value is 2800 or more, it is judged to have excellent magnetic properties in a DC magnetic field and to be acceptable (○). m If the value was less than 2800, it was judged as a failure (×).
[0083] The AC magnetic measurement conditions were a magnetic field peak value of 0.8 kA / m and a measurement frequency of 1.0 kHz. A maximum magnetic flux density of 0.80 T or more was judged to have excellent magnetic properties in an AC magnetic field and to pass (○). A maximum magnetic flux density of less than 0.80 T was judged to fail (×).
[0084] The results are shown in Tables 2A and 2B. It can be seen that if the composition and Si+Al≧0.50 (Si and Al indicate the mass percentage concentration of each element) are satisfied, and the area ratio of each crystal orientation is also satisfied, the JASO-CCT test results and the magnetic properties in a DC magnetic field and an AC magnetic field will pass ("○"). However, Nos. A11, A19, and A25 to A28 are reference examples.
[0085] In Comparative Examples B1 to B4, the Si+Al≧0.50 (Si and Al indicate the mass% concentration of each element) or Ni content was not satisfied, and the evaluation results for both corrosion resistance and magnetic properties were “×.” In particular, those that did not satisfy the Si+Al content did not satisfy the AC magnetic properties, and those that did not satisfy the Ni content did not satisfy the DC magnetic properties.
[0086] In Comparative Examples B5 to B8, the annealing temperature of the hot-rolled sheet was low and there were few coarse grains, so the area ratio of the {100}±15° orientation grains was less than 2.0%, and C / (A+B)≦15.0 was not satisfied, and the DC magnetic properties were also not satisfied. In B5, B7, and B8, there was little accumulation of strain in the coarse grains, so the area ratio of the {110}±15° orientation grains was also less than 2.0%.
[0087] In Comparative Examples B9 to B12, the annealing temperature of the cold-rolled sheet was high, so that the {111}±15° orientation grains grew significantly compared to the {110}±15° orientation grains and the {100}±15° orientation grains, and C / (A+B)≦15.0 was not satisfied. Furthermore, FeTiP and other precipitates that inhibit the growth of the {111} orientation were precipitated coarsely. As a result, the growth of the {111} orientation could not be inhibited during magnetic annealing, and the magnetic properties of the DC magnetic field were not satisfied. In Comparative Examples B13 to B15, the reduction ratio during cold rolling was low, so that recrystallization of the {110}±15° orientation grains during cold rolling was insufficient, and the magnetic properties in a DC magnetic field were not satisfactory.
[0088] [Table 1A]
[0089] [Table 1B]
[0090] [Table 2A]
[0091] [Table 2B] [Industrial Applicability]
[0092] The ferritic stainless steel of the present invention is capable of achieving both corrosion resistance and magnetic properties in DC and AC magnetic fields, and can therefore be suitably used in motor parts such as motor cases and motor cores for stepping motors and hysteresis motors, sensors such as electronic throttle sensors and EPS sensors, injectors, relays, solenoid valves, and their cores, yokes, connectors, housings, etc. In other words, the present invention is extremely useful industrially.
Claims
1. In mass percent, C: 0.001-0.030%, Si: 0.01-3.00%, Mn: 0.01 to 2.00%, P: 0.030% or less, S: 0.0050% or less, Ni: 0.05-3.00%, Cr: 5.0-18.0%, Al: 0.054-5.000%, V: 0.001-1.000%, B: 0.0001 to 0.0100%, and N: 0.001 to 0.030%; Further, it contains one or two of Ti: 0.01 to 0.30% and Nb: 0.001 to 0.60%, with the balance being Fe and impurities, and satisfies Si + Al ≧ 0.50; A ferritic stainless steel sheet characterized in that the texture on the sheet surface satisfies the following (a) to (c): (a) The area ratio of {110}±15° orientation grains on the sheet surface, in which the angle difference between the normal direction to the steel sheet surface and the {110} plane orientation is within 15°, is more than 2.0% and less than 20.0%. (b) The area ratio of {100}±15° orientation grains on the sheet surface, in which the angle difference between the normal direction to the steel sheet surface and the {100} plane orientation is within 15°, is more than 2.0% and less than 20.0%. (c) On the sheet surface, when the area ratio of {110}±15° oriented grains is A, the area ratio of {100}±15° oriented grains is B, and the area ratio of {111}±15° oriented grains on the sheet surface, in which the angle difference between the normal direction to the steel sheet surface and the {111} plane orientation is within 15°, C / (A+B)≦15.
0.
2. Further, replacing a part of Fe, by mass%, Mo: 0.01-3.00%, Sn: 0.001 to 3.00%, Cu: 0.01-3.00%, W: 0.001-1.00%, Sb: 0.001 to 0.100%, Co: 0.001 to 0.500%, Ca: 0.0001-0.0050%, Mg: 0.0001 to 0.0050%, Zr: 0.0001 to 0.0300%, Ga: 0.0001-0.0100%, Ta: 0.001 to 0.050%, REM: 0.001~0.100% 2. The ferritic stainless steel sheet according to claim 1, further comprising one or more of the following:
Citation Information
Patent Citations
Ferritic stainless steel and method for producing same
EP3093362A1
High cold forgeability electric stainless steel
JP1992318153A
Ferritic stainless steel excellent in magnetic property
JP1995233452A
Stainless steel stock for high hardness soft magnetic parts improved in workability
JP1997263902A
Production of ferritic stainless steel plate excellent in magnetic property
JP1999061255A